REDUCTION OF U(VI) TO U(IV) ON THE SURFACE OF MAGNETITE - Scott T.B.; Allen G.C.; Heard P.J.; Randell M.G. (My University, 2005)
To increase the understanding of uranium transport in the environment and in the presence of steel corrosion products, the interaction of U(VI) with natural magnetite has been studied. Sorption studies have been carried out using X-ray photoelectron spectroscopy (XPS) and secondary ion mass spectrometry (SIMS). The XPS results clearly indicate the reduction of U(VI) to U(IV) on the surface of magnetite facilitated by electron transfer between the Fe and U, leading to a coupled oxidation of Fe(II) to Fe(III).